The role of animal welfare in improving the future of farming - Doyle, Rebecca; Campbell, A.J.D.; Dione, Michel M.; Woodruff, M.; Muñoz, Camila; Alemayehu, Gezahegn; Berhe, Tsega; Knight-Jones, Theodore J.D. (Commonwealth Scientific and Industrial Research Organisation, 2022)
Context: Animal production plays a critical role in many global challenges around sustainability, including climate change and resilience, One Health and food security. With this role comes pressures on livestock welfare.